PURCHASE INTENTION AS A MEDIATOR BETWEEN SOCIAL MEDIA MARKETING AND MARKETPLACE IN PURCHASE CONVERSION, WITH PERCEIVED SCARCITY AS A MODERATOR: (A STUDY IN KUPANG CITY, EAST NUSA TENGGARA) - Klaasvakumok Jehezkielomi Kamuri; Noldy Danny Paul Mumu (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: Digital transformation has significantly altered the marketing landscape and consumer behavior, with social media and online platforms becoming the primary venues for interaction between businesses and the public. This change not only presents new opportunities but also challenges in converting consumer interest into actual purchases. This research explores how consumer engagement in the digital world contributes to purchasing decisions and how perceptions of product limitations strengthen that relationship.Methods: Using a quantitative approach through an explanatory research design, data were collected from 180 respondents from the Kupang City community using closed questionnaires and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method.Results: The research results indicate that marketing activities on social media and digital platforms have a significant influence on purchasing decisions, both directly and indirectly through increased consumer interest. The findings also indicate that the perception of product exclusivity (scarcity) can strengthen the urge to make a purchase.Conclusion and suggestion: The implications of this research emphasize the importance of digital communication strategies that focus on creating value, trust, and urgency in building purchasing decisions in a competitive digital environment, especially in the context of developing local areas like Kupang City. Keywords: Digital Consumer Behavior, Marketing Communication, Online Interaction,  Product Exclusivity, Purchase Conversion